A theory of multiformat communication: mechanisms, dynamics, and strategies - Moffett, Jordan W.; Folse, Judith Anne Garretson; Palmatier, Robert W. (Journal of the Academy of Marketing Science, 2021)
Extant communication theories predate the explosion of digital formats and technological advances such as virtual reality, which likely explains their predominant focus on traditional and format-level (e.g., face-to-face, email) rather than digital or characteristic-level (e.g., visual cues, synchronicity) design decisions. Firms thus lack insights into how to create and use emerging digital formats, individually or synergistically. To establish a holistic framework of bilateral multiformat communication for relationship marketing, this article reviews communication theory to establish a foundation for understanding multiformat communication and to identify any gaps (e.g., AI agents, simulated cues). The authors then review bilateral communication research in light of the identified theoretical gaps, to inform their framework. Finally, by decomposing these formats according to six fundamental characteristics, they predict how each characteristic might promote effective, efficient, and experiential communication goals, in light of distinct message, temporal, and dyadic factors. Ultimately, these combined insights reveal an overarching framework, with characteristic-level propositions grouped into five key themes, that can serve as a platform for academics and managers to develop multiformat communication theory and relationship strategies.